Effects of rTMS Treatment on Cognitive Impairment and Resting-State Brain Activity in Stroke Patients: A Randomized Clinical Trial - Yin, Mingyu; Liu, Yuanwen; Zhang, Liying; Zheng, Haiqing; Peng, Lingrong; Ai, Yinan; Luo, Jing; Hu, Xiquan (Frontiers in Neural Circuits, 2020)
Background: Repetitive transcranial magnetic stimulation (rTMS) has been employed for motor function rehabilitation for stroke patients, but its effects on post-stroke cognitive impairment (PSCI) remains controversial. Objective: To identify the effects of rTMS intervention on PSCI patients and its potential neural correlates to behavioral improvements. Methods: We recruited 34 PSCI patients for 20 sessions of 10 Hz rTMS or no-stim control treatments over the left dorsal lateral prefrontal cortex (DLPFC). Cognitive function was evaluated with the Montreal Cognitive Assessment Scale, Victoria Stroop Test, Rivermead Behaviour Memory Test and Activities of Daily Living (ADL) assessed with the Modified Barthel Index. 14 patients received functional magnetic resonance imaging scan, a useful noninvasive technique of determining how structurally segregated and functionally specialized brain area were interconnected, which was reflected by blood oxygenation level-dependent signals. The amplitude of low-frequency fluctuation (ALFF) and functional connectivity (FC) were applied as the analytical approaches, which were used to measure the resting-state brain activity and functional connection. Results: rTMS improved cognitive functions and ADLs for PSCI patients relative to patients that received no-stim control treatment. The cognitive improvements correlated to increased ALFF of the left medial prefrontal cortex, and increased FC of right medial prefrontal cortex and right ventral anterior cingulate cortex. Conclusions: 10Hz rTMS at DLPFC could improve cognitive function and quality of life for PSCI patients, which is associated with an altered frontal cortical activity.